2018
DOI: 10.1103/physrevb.97.054511
|View full text |Cite
|
Sign up to set email alerts
|

Doping evolution of the second magnetization peak and magnetic relaxation in (Ba1xKx)F

Abstract: We present a thorough study of doping dependent magnetic hysteresis and relaxation characteristics in single crystals of (Ba 1-x K x )Fe 2 As 2 (0.18≤x≤1). The critical current density J c reaches maximum in the underdoped sample x=0.26 and then decreases in the optimally doped and overdoped samples. Meanwhile, magnetic relaxation rate S rapidly increases and the flux creep activation barrier U 0 sharply decreases in the overdoped sample x=0.70. These results suggest that vortex pinning is very strong in the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 86 publications
1
9
0
Order By: Relevance
“…The improved quality of iron-based superconducting single crystals 49,50 made possible the observation of ordered vortex phases 34,50,51 . It is now established that the overdoped 122-type specimens exhibit a relatively weak, pointlike δT c pinning 52 and a pronounced SMP develops 31 . The P-Ba122 single crystals analysed in this work have been grown by the Ba 2 As 3 /Ba 2 P 3 -flux method 53 at the Institute of Physics, Chinese Academy of Sciences.…”
Section: Methodsmentioning
confidence: 99%
“…The improved quality of iron-based superconducting single crystals 49,50 made possible the observation of ordered vortex phases 34,50,51 . It is now established that the overdoped 122-type specimens exhibit a relatively weak, pointlike δT c pinning 52 and a pronounced SMP develops 31 . The P-Ba122 single crystals analysed in this work have been grown by the Ba 2 As 3 /Ba 2 P 3 -flux method 53 at the Institute of Physics, Chinese Academy of Sciences.…”
Section: Methodsmentioning
confidence: 99%
“…J c , depending on the disorder, either decreases monotonically or displays a second peak (SP) in the magnetization, also called a "fishtail" [9,10]. Interestingly, the existence of the SP is found to be dopingdependent [11]. Therefore understanding the superconducting J c is a central issues pertaining to both fundamental science as well as technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism responsible for SMP in Ni-doped BaFe 2 As 2 pnictide superconductors is as yet unresolved [29,36,37]. Interestingly, in iron-pnictide superconductors, it has been observed that the existence of the SMP is doping dependent [31,38].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, pnictides are known as multiband superconductors, which may play a role on the pinning of vortices through the inter-band and intra-band electron scatterings [23]. Since then, vortex dynamics studies were performed on different pnictides compounds discovered over the years [13,[24][25][26][27][28][29][30][31], and, most of them are devoted to the study of the mechanism responsible for the appearance of SMP in isothermal magnetization curves. Contrary to the cuprates, where the SMP is mostly observed only for H c-axis, in Fe-pnictides, due to the low anisotropy, it is observed for both, H c-axis and H ab planes.…”
Section: Introductionmentioning
confidence: 99%